A quasi-solid electrolyte for aqueous zinc ion batteries and its preparation method and application
By using a combination of aluminum pillared montmorillonite and zinc salt manganese salt in aqueous zinc ion batteries, the electrolyte layer spacing and increase specific surface area are broadened, and the battery capacity attenuation and cycle stability are solved, and efficient zinc ions are achieved Transmission and battery safety performance improvements.
Patent Information
- Application Number
- CN202210519060.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The all-solid electrolyte of existing aqueous zinc ion batteries has low ion conductivity, high preparation cost, and complex process. The montmorillonite layer spacing is not enough to meet the demand for rapid zinc ions, resulting in poor capacity attenuation and cycle stability.
Aluminum column-supported montmorillonite is used to prepare aqueous zinc ions by inserting hydrated aluminum ions with a larger ion radius into the SiO4-AlO6-SiO4 layers of montmorillonite to broaden the layer spacing and increase the specific surface area. Battery quasi-solid electrolyte.
It significantly improves the rapid and stable transmission of zinc ions and the stability of deep cycling structure, optimizes the reversible capacity and cycling stability of the battery, reduces production costs, simplifies the preparation process, and improves the safety performance of the battery.
Smart Images

Figure CN115020827B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy materials and relates to a quasi-solid electrolyte for an aqueous zinc ion battery, and in particular to a quasi-solid electrolyte for an aqueous zinc ion battery and a preparation method and application thereof. Background Art
[0002] The growing demand for green and sustainable energy storage, such as portable electronic devices and grid-scale energy storage systems, has stimulated the development of advanced energy storage technologies. Zinc is abundant, low-cost and non-toxic. Aqueous zinc-ion batteries have the advantages of high theoretical capacity, high safety, low electrochemical potential (-0.763 V compared to the standard hydrogen electrode (SHE), convenient assembly of aqueous zinc-ion batteries (can be assembled in air) and adaptability to large-scale production. However, rechargeable aqueous zinc-ion batteries have serious capacity decay, corrosion of the zinc anode by the aqueous electrolyte, side reactions that form a passivation layer, formation of zinc dendrites and internal short-circuit failures, which have always plagued the practical application of rechargeable aqueous zinc-ion batteries.
[0003] All-solid or quasi-solid electrolytes can effectively overcome the above problems of rechargeable aqueous zinc-ion batteries. The research on solid electrolytes mainly focuses on all-solid electrolytes and quasi-solid electrolytes. Due to the problems of excessive interface resistance, high cost and low ionic conductivity of all-solid electrolytes, its further development is hindered. Quasi-solid electrolytes are generally composed of liquid electrolytes and polymer matrices, which have both the strong mechanical properties of solid electrolytes and the diffusion characteristics of liquid electrolytes. Traditional polymer matrices include polyvinyl alcohol (PVA), polyacrylamide (PAM) and polyethylene glycol (PEG), which generally need to be obtained by low-temperature freezing polymerization or high-temperature polymerization in the presence of initiators and cross-linking agents, and most of them require multiple polymerizations to obtain. The obtained polymer matrix generally needs to be immersed in a liquid electrolyte for more than 12 hours to fully replace the zinc ions. The above-mentioned methods have a series of problems, such as: the cost of raw materials is too high, the preparation process is complicated, low-temperature or high-temperature environment is required, the overall reaction time is too long and the ionic conductivity is low. There are very few methods that can add electrolytes into the matrix during the polymerization of polymer monomers, but this brings new problems such as decreased battery performance and poor cycle stability.
[0004] Montmorillonite is a clay with a 2:1 layered silicate structure, each layer consisting of two thin layers of SiO4 tetrahedrons with a thin layer of AlO6 octahedron sandwiched between them. 3+ Mg 2+In order to balance the excess negative charge, some free-moving cations (such as Na + and Ca 2+ ) are located between the SiO4-AlO6-SiO4 layers. It is worth noting that these cations (such as Na + and Ca 2+ ), can be combined with Zn 2+ Ion exchange occurs, thus Zn 2+ Because montmorillonite has good electronic insulation (can prevent short circuit between positive and negative electrodes), and also has good Zn 2+ Ion transport performance, so it has great application potential as a quasi-solid electrolyte for aqueous zinc-ion batteries. A new type of palygorskite-based inorganic colloidal electrolyte for aqueous zinc-ion batteries, which can provide good protection for the cathode / anode, inhibit the dissolution of MnO2, the production of irreversible byproducts and dendrite growth. Using montmorillonite as a protective coating for the cathode / anode can produce an aqueous zinc-ion battery with excellent electrochemical performance. However, most of these montmorillonites used in aqueous zinc-ion batteries use original montmorillonite or zinc-pre-intercalated montmorillonite. The SiO4-AlO6-SiO4 interlayer spacing (1.3-1.5nm) of original montmorillonite and zinc-pre-intercalated montmorillonite is relatively small, which is not enough to meet the Zn requirement of aqueous zinc-ion batteries. 2+ The requirement for fast transport, and as Zn 2+ The montmorillonite layers in the long-term transport channel (long battery cycle) also lack strong support, which is not conducive to rate performance and long-term cycle performance.
[0005] CN111463481A discloses a composite quasi-solid electrolyte, a preparation method and a full battery. The composite quasi-solid electrolyte is composed of mesoporous SiO2 nanoparticles and organic polymers, and the mass ratio of mesoporous SiO2 nanoparticles to organic polymers is (0.02-1):1. The high molecular polymer is one or a mixture of PVDF, PVDF-HFP, PEO, PAA, PAN, PDMS or PMMA. A certain amount of electrolyte is stored by means of the mesoporous structure of SiO2, and a three-dimensional ion channel is formed, thereby ensuring efficient and rapid charge transfer properties inside the electrolyte. The present invention solves the problems of low ion conductivity and poor interface compatibility of traditional solid electrolytes, and can significantly improve the rate performance and cycle stability of the battery. It can be applied to various secondary ion batteries such as lithium metal batteries, lithium ion batteries, sodium ion batteries, zinc ion batteries, etc. However, the composite quasi-solid electrolyte has low ion conductivity and high preparation cost.
[0006] CN107645013A discloses a composite quasi-solid electrolyte, a composite quasi-solid electrolyte membrane and a preparation method thereof, and a lithium battery or lithium ion battery comprising the composite quasi-solid electrolyte membrane. The composite quasi-solid electrolyte of the invention comprises a solid electrolyte, a liquid electrolyte containing a lithium salt, inorganic nanoparticles, and a binder. However, the preparation method of the composite quasi-solid electrolyte is complicated and is not suitable for large-scale promotion and use.
[0007] CN101013766 discloses a quasi-solid electrolyte and its preparation method and application. The quasi-solid electrolyte includes main components such as ionic liquid, inorganic layered material, elemental iodine, iodide, photoanode complexing agent and guanidine isothiocyanate, and can be prepared by direct mixing method or organic solvent mixed volatilization method, wherein the ionic liquid is the solvent, and the molar concentrations of other components are: inorganic layered material 0.001-10 mol / L, elemental iodine 0.01-1 mol / L, iodide 0.01-10 mol / L, photoanode complexing agent 0.01-1 mol / L, guanidine isothiocyanate 0.01-1 mol / L. However, the ionic conductivity of the quasi-solid electrolyte is low.
[0008] In summary, although all-solid-state electrolytes and quasi-solid-state electrolytes effectively overcome the problems of aqueous electrolytes in rechargeable aqueous zinc-ion batteries that can corrode the zinc anode, form a passivation layer, form zinc dendrites, and cause internal short-circuit failures, the existing technology for preparing all-solid-state electrolytes and polymer quasi-solid-state electrolytes for aqueous zinc-ion batteries has low ionic conductivity, high method cost, complex process, and does not meet the requirements of industrialization; although montmorillonite or zinc pre-intercalated montmorillonite is cheap, the interlayer spacing (1.3-1.5 nm) is relatively small, which is not enough to meet the requirements of aqueous zinc-ion batteries Zn 2+ The requirement for fast transport, and as Zn 2+ The montmorillonite layers in the long-term transport channel (long battery cycle) also lack strong support and cannot meet the industrialization requirements of high-performance aqueous zinc-ion batteries. Therefore, there is still a lack of effective solutions for quasi-solid electrolytes for aqueous zinc-ion batteries. It is very important to develop and design a new type of quasi-solid electrolyte for aqueous zinc-ion batteries and its preparation method. Summary of the invention
[0009] In view of the shortcomings of the prior art, the present invention aims to provide a quasi-solid electrolyte for aqueous zinc ion batteries and a preparation method and application thereof. In the aluminum-pillared montmorillonite of the present invention, hydrated aluminum ions (hydroxyaluminum ions) with larger ionic radius are inserted into the SiO4-AlO6-SiO4 interlayer of the montmorillonite as pillaring agents, which significantly widens the interlayer spacing and ensures that Zn in the quasi-solid electrolyte for aqueous zinc ion batteries is 2+The invention provides fast and stable transmission and structural stability after deep cycling; the widening of the interlayer spacing correspondingly brings about an expansion of the specific surface area, provides more active sites, and shortens the transmission path of zinc ions; the aqueous zinc ion battery assembled using the aqueous zinc ion battery quasi-solid electrolyte of the invention has excellent reversible capacity and cycle stability.
[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a quasi-solid electrolyte for an aqueous zinc ion battery, wherein the quasi-solid electrolyte for an aqueous zinc ion battery comprises a zinc salt, a manganese salt and an aluminum-pillared montmorillonite.
[0012] In the aluminum-pillared montmorillonite of the present invention, hydrated aluminum ions (hydroxyaluminum ions) with larger ionic radius are inserted into the SiO4-AlO6-SiO4 interlayer of the montmorillonite as pillaring agents, which significantly widens the interlayer spacing and ensures that Zn in the quasi-solid electrolyte of the aqueous zinc ion battery 2+ The invention provides a fast and stable transmission and structural stability after deep cycling; the widening of the interlayer spacing correspondingly brings about an expansion of the specific surface area, provides more active sites, and shortens the transmission path of zinc ions; the aqueous zinc ion battery assembled with the quasi-solid electrolyte of the aqueous zinc ion battery of the present invention has excellent discharge specific capacity, coulomb efficiency and capacity retention rate.
[0013] Preferably, the preparation method of the aluminum pillared montmorillonite comprises the following steps:
[0014] (1) mixing an aluminum chloride solution and a sodium hydroxide solution, and allowing the mixture to stand to obtain an aluminum pillaring solution;
[0015] (2) mixing montmorillonite with water to obtain a montmorillonite suspension; then mixing the montmorillonite suspension with the aluminum pillared solution obtained in step (1), allowing the mixture to stand, to obtain the aluminum pillared montmorillonite.
[0016] The invention adopts aluminum chloride solution, sodium hydroxide solution and montmorillonite as main raw materials to prepare aluminum pillared montmorillonite. The raw materials used in the preparation method are widely available and inexpensive.
[0017] Preferably, the mixing in step (1) includes a first mixing and a second mixing performed sequentially.
[0018] Preferably, the temperature of the first mixing is 10-30° C., and the time is 1-10 min.
[0019] The temperature of the first mixing is 10-30°C, for example, it can be 10°C, 12°C, 15°C, 17°C, 20°C, 22°C, 25°C, 27°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] The first mixing time is 1 to 10 minutes, for example, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the temperature of the second mixing is 40-80° C., and the time is 1-4 hours.
[0022] The temperature of the second mixing is 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] The second mixing time is 1 to 4 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the first mixing or second mixing method comprises stirring and / or ultrasound, respectively and independently.
[0025] Preferably, the standing temperature in step (1) is 40 to 80° C. and the standing time is 12 to 36 hours.
[0026] The standing temperature in step (1) is 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] The standing time in step (1) is 12 to 36 hours, for example, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours or 36 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the volume ratio of the aluminum chloride solution to the sodium hydroxide solution in step (1) is 1:(1-1.4), for example, it can be 1:1, 1:1.05, 1:1.1, 1:15, 1:1.2, 1:1.25, 1:1.3, 1:1.35 or 1:1.4, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the concentration of the aluminum chloride solution in step (1) is 10 to 15 g / L, for example, 10 g / L, 10.5 g / L, 11 g / L, 11.5 g / L, 12 g / L, 12.5 g / L, 13 g / L, 13.5 g / L, 14 g / L, 14.5 g / L or 15 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, the concentration of the sodium hydroxide solution in step (1) is 6 to 10 g / L, for example, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L or 10 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the solid-to-liquid ratio of the montmorillonite to water in step (2) is (1-5):100, for example, it can be 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100 or 5:100, and the unit of the solid-to-liquid ratio is g / mL.
[0032] Preferably, the volume ratio of the montmorillonite suspension to the aluminum pillared solution is 10:(5.5-42), for example, it can be 10:5.5, 10:6, 10:8, 10:10, 10:12, 10:14, 10:16, 10:18, 10:20, 10:22, 10:24, 10:26, 10:28, 10:30, 10:32, 10:34, 10:36, 10:38, 10:40 or 10:42, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the mixing temperature in step (2) is 40 to 80° C. and the mixing time is 1 to 4 hours;
[0034] The mixing temperature in step (2) is 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] The mixing time in step (2) is 1 to 4 hours, for example, 1 hour, 1.2 hours, 1.5 hours, 1.7 hours, 2 hours, 2.2 hours, 2.51 hours, 2.7 hours, 3 hours, 3.2 hours, 3.5 hours, 3.7 hours or 4 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] Preferably, the mixing method in step (2) includes stirring and / or ultrasound.
[0037] Preferably, the standing temperature in step (2) is 40 to 80° C. and the standing time is 6 to 18 hours.
[0038] The standing temperature in step (2) is 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] The standing time in step (2) is 6 to 18 hours, for example, it can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours or 18 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] Preferably, after the standing, step (2) further comprises centrifugation, washing, drying, grinding and screening in sequence.
[0041] The centrifugation, washing, drying, grinding and sieving described in the present invention are all conventional operations in the art, and the present invention is not specifically limited here. Among them, a 0.1 mol / L silver nitrate solution is used to detect the removal of chloride ions, and the centrifugation and washing are used to remove chloride ions until no precipitation occurs in the silver nitrate solution test.
[0042] Exemplarily, the drying temperature is 50-70°C, for example, 50°C, 52°C, 55°C, 57°C, 60°C, 62°C, 65°C, 67°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In a second aspect, the present invention provides a method for preparing a quasi-solid electrolyte for an aqueous zinc ion battery as described in the first aspect, the preparation method comprising:
[0044] Mixing the electrolyte solution and the aluminum pillared montmorillonite, and allowing to stand, to obtain a quasi-solid electrolyte for an aqueous zinc ion battery;
[0045] The electrolyte solution includes zinc salt and manganese salt.
[0046] The method for preparing the quasi-solid electrolyte for aqueous zinc ion batteries of the present invention has simple process, low experimental condition requirements, cheap raw materials, low production cost and meets the requirements of industrialization.
[0047] Preferably, the mixing temperature is 10-30° C. and the mixing time is 40-80 min.
[0048] The temperature of the mixed electrolyte solution and aluminum-pillared montmorillonite is 10-30°C, for example, 10°C, 12°C, 15°C, 17°C, 20°C, 22°C, 25°C, 27°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] The time for mixing the electrolyte solution and the aluminum-pillared montmorillonite is 40 to 80 minutes, for example, it can be 40 minutes, 42 minutes, 45 minutes, 47 minutes, 50 minutes, 52 minutes, 55 minutes, 57 minutes, 60 minutes, 62 minutes, 65 minutes, 67 minutes, 70 minutes, 75 minutes or 80 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the mixing method comprises stirring and / or ultrasound.
[0051] Preferably, the standing temperature is 10-30° C. and the standing time is 8-12 hours.
[0052] The standing temperature is 10-30°C, for example, 10°C, 12°C, 15°C, 17°C, 20°C, 22°C, 25°C, 27°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] The standing time is 8 to 12 hours, for example, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the liquid-to-solid ratio of the electrolyte solution to the aluminum-pillared montmorillonite is (5-10):3, for example, it can be 5:3, 5.5:3, 6:3, 6.5:3, 7:3, 7.5:3, 8:3, 8.5:3, 9:3, 9.5:3 or 10:3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The unit of the liquid-to-solid ratio is g / g. When the solid-liquid ratio of the electrolyte solution to the aluminum-pillared montmorillonite is too low, the discharge specific capacity, the coulombic efficiency and the capacity retention rate will decrease. This is because the content of the aluminum-pillared montmorillonite is too little and the ionic conductivity is too low, resulting in a smaller discharge specific capacity; the gel degree of the quasi-solid electrolyte is not enough, resulting in insufficient protection of the quasi-solid electrolyte for the positive and negative electrodes, leading to the growth of dendrites and the dissolution of the positive electrode material, resulting in low coulombic efficiency and a decrease in capacity retention rate; when the solid-liquid ratio of the electrolyte solution to the aluminum-pillared montmorillonite is too high, the discharge specific capacity, the coulombic efficiency and the capacity retention rate will decrease. This is because the content of the aluminum-pillared montmorillonite is too high, resulting in an increase in interface resistance and a decrease in ionic conductivity; the content of the liquid electrolyte decreases, and the concentration of free zinc ions decreases, resulting in a decrease in specific capacity, coulombic efficiency and capacity retention rate.
[0055] Preferably, the concentration of the zinc salt in the electrolyte solution is 1 to 3 mol / L, for example, it can be 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.7 mol / L, 2 mol / L, 2.2 mol / L, 2.5 mol / L, 2.7 mol / L or 3 mol / L, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable; when the concentration of the zinc salt is low, the discharge specific capacity, the coulomb efficiency and the capacity retention rate will be reduced, because the ionic conductivity of the zinc ions is reduced, the number of zinc ions is too small, and more zinc ions cannot be provided to enter the manganese oxide; when the concentration of the zinc salt is high, the discharge specific capacity, the coulomb efficiency and the capacity retention rate will be reduced, because the concentration of the zinc salt solution increases, the viscosity increases, the ionic conductivity of the zinc ions decreases, and too many zinc ions will block the tunnel structure of the manganese oxide, which is not conducive to charging and discharging.
[0056] Preferably, the zinc salt comprises any one of zinc sulfate, zinc chloride, zinc bromide, zinc iodide, zinc nitrate, zinc acetate or zinc trifluoromethanesulfonate or a combination of at least two thereof, and typical but non-limiting combinations include a combination of zinc sulfate and zinc chloride, a combination of zinc chloride and zinc bromide, a combination of zinc iodide and zinc nitrate, a combination of zinc nitrate and zinc acetate, a combination of zinc acetate and zinc trifluoromethanesulfonate, a combination of zinc sulfate, zinc chloride and zinc bromide, or a combination of zinc chloride, zinc bromide, zinc iodide and zinc nitrate.
[0057] Preferably, the concentration of manganese salt in the electrolyte solution is 0.1-0.3 mol / L, for example, it can be 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.17 mol / L, 0.2 mol / L, 0.22 mol / L, 0.25 mol / L, 0.27 mol / L or 0.3 mol / L, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable; when the concentration of manganese salt is low, the discharge specific capacity, coulomb efficiency and capacity retention rate will be reduced, which is because the dissolution inhibition ability of manganese sulfate on the positive electrode manganese oxide is weakened, resulting in more manganese ions being dissolved, resulting in a corresponding decrease in discharge specific capacity and a decrease in capacity retention rate; when the concentration of manganese salt is high, the discharge specific capacity, coulomb efficiency and capacity retention rate will be reduced, which is because the concentration of manganese sulfate is too high, which will lead to an excessively high concentration of the overall solution, resulting in salting out, and zinc sulfate and manganese sulfate will precipitate and cover the positive and negative electrode surfaces, resulting in an increase in interface resistance. In addition, it will lead to increased costs.
[0058] Preferably, the manganese salt comprises any one of manganese sulfate, manganese chloride, manganese bromide, manganese iodide, manganese nitrate, manganese acetate or manganese trifluoromethanesulfonate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of manganese sulfate and manganese chloride, a combination of manganese chloride and manganese bromide, a combination of manganese bromide and manganese iodide, a combination of manganese nitrate and manganese acetate, a combination of manganese acetate and manganese trifluoromethanesulfonate, a combination of manganese sulfate, manganese chloride and manganese bromide, or a combination of manganese chloride, manganese bromide, manganese iodide and manganese nitrate.
[0059] As a preferred technical solution of the preparation method described in the second aspect of the present invention, the preparation method comprises the following steps:
[0060] An electrolyte solution and aluminum pillared montmorillonite having a liquid-to-solid ratio of (5-10):3 are mixed by stirring and / or ultrasonic mixing at 10-30° C. for 40-80 minutes, and then allowed to stand at 10-30° C. for 8-12 hours to obtain a quasi-solid electrolyte for an aqueous zinc ion battery; the unit of the solid-to-liquid ratio is g / g; the electrolyte solution comprises a zinc salt having a concentration of 1-3 mol / L and a manganese salt having a concentration of 0.1-0.3 mol / L;
[0061] The aluminum pillared montmorillonite is prepared by the following preparation method:
[0062] (1) mixing an aluminum chloride solution having a concentration of 10 to 15 g / L and a sodium hydroxide solution having a concentration of 6 to 10 g / L in a volume ratio of 1:(1 to 1.4), and standing at 40 to 80° C. for 12 to 36 hours to obtain an aluminum pillaring solution; the mixing includes a first mixing and a second mixing performed sequentially; the first mixing temperature is 10 to 30° C., and the time is 1 to 10 minutes; the second mixing temperature is 40 to 80° C., and the time is 1 to 4 hours;
[0063] (2) mixing montmorillonite and water in a solid-liquid ratio of (1-5):100 to obtain a montmorillonite suspension; then mixing the montmorillonite suspension with the aluminum pillared solution obtained in step (1) in a volume ratio of 10:(5.5-42); standing at 40-80° C. for 6-18 hours, and then centrifuging, washing, drying, grinding and sieving in sequence to obtain the aluminum pillared montmorillonite; the unit of the solid-liquid ratio is g / mL.
[0064] In a third aspect, the present invention provides an application of a quasi-solid electrolyte for an aqueous zinc ion battery as described in the first aspect, the application comprising: coating the quasi-solid electrolyte for an aqueous zinc ion battery on the surfaces of a first electrode and a second electrode respectively to obtain a positive electrode and a negative electrode; and assembling the positive electrode, the negative electrode and a diaphragm to obtain an aqueous zinc ion battery.
[0065] The coating method of the present invention includes but is not limited to coating with a scraper.
[0066] Preferably, the first electrode comprises a manganese oxide electrode.
[0067] Preferably, the second electrode comprises a zinc electrode.
[0068] Preferably, the membrane comprises a glass fiber membrane.
[0069] The present invention obtains a positive electrode and a negative electrode with a protective layer by coating a quasi-solid electrolyte of an aqueous zinc ion battery on the surface of a manganese oxide electrode and a zinc electrode, thereby preventing the acidic aqueous electrolyte from directly contacting the manganese oxide electrode and the zinc electrode, thereby inhibiting the dissolution of the manganese oxide electrode, the corrosion of the zinc electrode and the side reaction of forming a passivation layer, avoiding the problems of rapid capacity decay and internal short circuit failure of the aqueous zinc ion battery, and effectively improving the safety performance of the aqueous zinc ion battery.
[0070] Compared with the prior art, the present invention has the following beneficial effects:
[0071] (1) In the aluminum-pillared montmorillonite of the present invention, hydrated aluminum ions (hydroxyaluminum ions) with larger ionic radius are inserted into the SiO4-AlO6-SiO4 interlayer of the montmorillonite as pillaring agents, which significantly widens the interlayer spacing and ensures that Zn in the quasi-solid electrolyte of the aqueous zinc ion battery 2+ The fast and stable transmission and structural stability after deep cycling; the widening of the interlayer spacing correspondingly brings about the expansion of the specific surface area, provides more active sites, and shortens the transmission path of zinc ions; the aqueous zinc ion battery assembled with the quasi-solid electrolyte of the aqueous zinc ion battery of the present invention has excellent reversible capacity and cycle stability;
[0072] (2) The present invention uses aluminum chloride solution, sodium hydroxide solution and montmorillonite as main raw materials to prepare aluminum pillared montmorillonite, which is then mixed with an electrolyte solution to prepare a quasi-solid electrolyte for an aqueous zinc ion battery; the raw materials used in the preparation method are widely available and inexpensive; the preparation method of the quasi-solid electrolyte for an aqueous zinc ion battery of the present invention has a simple process, low experimental conditions, low production cost and meets the requirements of industrialization;
[0073] (3) The present invention obtains a positive electrode and a negative electrode with a protective layer by coating a quasi-solid electrolyte of an aqueous zinc ion battery on the surface of a manganese oxide electrode and a zinc electrode, thereby preventing the acidic aqueous electrolyte from directly contacting the manganese oxide electrode and the zinc electrode, thereby inhibiting the dissolution of the manganese oxide electrode, the corrosion of the zinc electrode and the side reaction of forming a passivation layer, avoiding the problems of rapid capacity decay and internal short circuit failure of the aqueous zinc ion battery, and effectively improving the safety performance of the aqueous zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 It is the small-angle X-ray diffraction pattern of the aluminum-pillared montmorillonite in Examples 1 to 5 and the montmorillonite in Comparative Example 1.
[0075] Figure 2 It is the X-ray diffraction pattern of the standard diffraction card of montmorillonite, aluminum pillared montmorillonite and aqueous zinc ion battery quasi-solid electrolyte comparing ZnSO4 and montmorillonite in Example 1.
[0076] Figure 3 This is a TEM image of the quasi-solid electrolyte for an aqueous zinc ion battery prepared in Example 1.
[0077] Figure 4 This is a long cycle test chart of an aqueous zinc ion button cell assembled with a quasi-solid electrolyte for an aqueous zinc ion battery prepared in Example 1 at a current density of 0.5 A / g. DETAILED DESCRIPTION
[0078] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0079] Example 1
[0080] The present embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, wherein the quasi-solid electrolyte for an aqueous zinc ion battery comprises zinc sulfate, manganese sulfate and aluminum-pillared montmorillonite.
[0081] The preparation method of the aqueous zinc ion battery quasi-solid electrolyte comprises:
[0082] An electrolyte solution and aluminum-pillared montmorillonite having a liquid-to-solid ratio of 7.5:3 are mixed by stirring for 20 minutes and ultrasonicating for 40 minutes at 20°C, wherein the unit of the solid-to-liquid ratio is g / g, and the electrolyte solution comprises zinc sulfate having a concentration of 2 mol / L and manganese sulfate having a concentration of 0.2 mol / L; the mixture is allowed to stand at 20°C for 10 hours to obtain a quasi-solid electrolyte for an aqueous zinc ion battery.
[0083] The preparation method of the aluminum pillared montmorillonite comprises the following steps:
[0084] (1) mixing an aluminum chloride solution and a sodium hydroxide solution in a volume ratio of 1:1.2 by stirring at 20° C. for 5 minutes, wherein the concentration of the aluminum chloride solution is 13 g / L and the concentration of the sodium hydroxide solution is 8 g / L; stirring at 60° C. for 3 hours; and standing and heating at 60° C. for 24 hours to obtain an aluminum pillaring solution;
[0085] (2) Mixing montmorillonite and water at a solid-liquid ratio of 2:100, wherein the unit of the solid-liquid ratio is g / mL, to obtain a montmorillonite suspension; mixing the montmorillonite suspension at a volume ratio of 10:22 with the aluminum pillaring solution obtained in step (1) by dropping the aluminum pillaring solution into the montmorillonite suspension; stirring at 60° C. for 3 h; standing and heating at 60° C. for 12 h; and centrifuging, washing, drying, grinding and sieving in sequence to obtain aluminum pillared montmorillonite.
[0086] Example 2
[0087] The present embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, wherein the quasi-solid electrolyte for an aqueous zinc ion battery comprises zinc chloride, manganese chloride and aluminum-pillared montmorillonite.
[0088] The preparation method of the aqueous zinc ion battery quasi-solid electrolyte comprises:
[0089] An electrolyte solution and aluminum-pillared montmorillonite having a liquid-to-solid ratio of 7:3 are mixed by stirring for 20 minutes and ultrasonically for 30 minutes at 25°C, wherein the unit of the solid-to-liquid ratio is g / g, and the electrolyte solution includes zinc chloride having a concentration of 1.5 mol / L and manganese chloride having a concentration of 0.15 mol / L; the mixture is allowed to stand at 25°C for 9 hours to obtain a quasi-solid electrolyte for an aqueous zinc ion battery.
[0090] The preparation method of the aluminum pillared montmorillonite comprises the following steps:
[0091] (1) mixing an aluminum chloride solution and a sodium hydroxide solution in a volume ratio of 1:1.2 at 15° C. by stirring for 3 minutes, wherein the concentration of the aluminum chloride solution is 11 g / L and the concentration of the sodium hydroxide solution is 8 g / L; stirring for 2 hours at 70° C.; and standing and heating at 60° C. for 18 hours to obtain an aluminum pillaring solution;
[0092] (2) Mixing montmorillonite and water at a solid-liquid ratio of 3:100, wherein the unit of the solid-liquid ratio is g / mL, to obtain a montmorillonite suspension; mixing the montmorillonite suspension at a volume ratio of 10:15 with the aluminum pillaring solution obtained in step (1) by dropping the aluminum pillaring solution into the montmorillonite suspension; stirring at 50° C. for 2 h; standing and heating at 50° C. for 12 h; and centrifuging, washing, drying, grinding and sieving in sequence to obtain aluminum pillared montmorillonite.
[0093] Example 3
[0094] The present embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, wherein the quasi-solid electrolyte for an aqueous zinc ion battery comprises zinc chloride, manganese nitrate and aluminum-pillared montmorillonite.
[0095] The preparation method of the aqueous zinc ion battery quasi-solid electrolyte comprises:
[0096] An electrolyte solution and aluminum-pillared montmorillonite having a liquid-to-solid ratio of 10:3 are mixed by stirring at 30° C. for 40 minutes, wherein the unit of the solid-to-liquid ratio is g / g, and the electrolyte solution comprises zinc chloride having a concentration of 1 mol / L and manganese nitrate having a concentration of 0.3 mol / L; the mixture is allowed to stand at 10° C. for 12 hours to obtain a quasi-solid electrolyte for an aqueous zinc ion battery.
[0097] The preparation method of the aluminum pillared montmorillonite comprises the following steps:
[0098] (1) mixing an aluminum chloride solution and a sodium hydroxide solution in a volume ratio of 1:1 by ultrasonic mixing at 10° C. for 10 min, wherein the concentration of the aluminum chloride solution is 15 g / L and the concentration of the sodium hydroxide solution is 10 g / L; ultrasonic mixing at 80° C. for 1 h; and standing and heating at 80° C. for 12 h to obtain an aluminum pillaring solution;
[0099] (2) Mixing montmorillonite and water at a solid-liquid ratio of 1:100, wherein the unit of the solid-liquid ratio is g / mL, to obtain a montmorillonite suspension; mixing the montmorillonite suspension at a volume ratio of 10:5.5 with the aluminum pillaring solution obtained in step (1) by dropping the aluminum pillaring solution into the montmorillonite suspension; stirring at 40° C. for 4 h; standing and heating at 80° C. for 6 h; and centrifuging, washing, drying, grinding and sieving in sequence to obtain aluminum pillared montmorillonite.
[0100] Example 4
[0101] The present embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, wherein the quasi-solid electrolyte for an aqueous zinc ion battery comprises zinc nitrate, manganese nitrate and aluminum-pillared montmorillonite.
[0102] The preparation method of the aqueous zinc ion battery quasi-solid electrolyte comprises:
[0103] An electrolyte solution and aluminum-pillared montmorillonite having a liquid-to-solid ratio of 5:3 are mixed by ultrasound at 10°C for 80 minutes, wherein the unit of the solid-to-liquid ratio is g / g, and the electrolyte solution comprises zinc nitrate having a concentration of 3 mol / L and manganese nitrate having a concentration of 0.1 mol / L; the mixture is allowed to stand at 30°C for 8 hours to obtain a quasi-solid electrolyte for an aqueous zinc ion battery.
[0104] The preparation method of the aluminum pillared montmorillonite comprises the following steps:
[0105] (1) mixing an aluminum chloride solution and a sodium hydroxide solution in a volume ratio of 1:1.4 by ultrasonic mixing at 30° C. for 1 min, wherein the concentration of the aluminum chloride solution is 10 g / L and the concentration of the sodium hydroxide solution is 6 g / L; stirring at 40° C. for 4 h; and standing and heating at 40° C. for 36 h to obtain an aluminum pillaring solution;
[0106] (2) Mixing montmorillonite and water at a solid-liquid ratio of 5:100, wherein the unit of the solid-liquid ratio is g / mL, to obtain a montmorillonite suspension; mixing the montmorillonite suspension at a volume ratio of 10:42 with the aluminum pillaring solution obtained in step (1) by dropping the aluminum pillaring solution into the montmorillonite suspension; stirring at 80° C. for 1 h; standing and heating at 40° C. for 18 h; and centrifuging, washing, drying, grinding and sieving in sequence to obtain aluminum pillared montmorillonite.
[0107] Example 5
[0108] The present embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, wherein the quasi-solid electrolyte for an aqueous zinc ion battery comprises zinc sulfate, manganese chloride and aluminum-pillared montmorillonite.
[0109] The preparation method of the aqueous zinc ion battery quasi-solid electrolyte comprises:
[0110] An electrolyte solution and aluminum-pillared montmorillonite having a liquid-to-solid ratio of 9:3 are mixed by stirring for 20 minutes and ultrasonically for 40 minutes at 15°C, wherein the unit of the solid-to-liquid ratio is g / g, and the electrolyte solution includes zinc sulfate having a concentration of 2 mol / L and manganese chloride having a concentration of 0.25 mol / L; the mixture is allowed to stand at 20°C for 11 hours to obtain a quasi-solid electrolyte for an aqueous zinc ion battery.
[0111] The preparation method of the aluminum pillared montmorillonite comprises the following steps:
[0112] (1) mixing an aluminum chloride solution and a sodium hydroxide solution in a volume ratio of 1:1.1 by stirring at 20° C. for 8 minutes, wherein the concentration of the aluminum chloride solution is 14 g / L and the concentration of the sodium hydroxide solution is 7 g / L; ultrasonicating at 50° C. for 3 hours; and standing and heating at 50° C. for 30 hours to obtain an aluminum pillaring solution;
[0113] (2) Mixing montmorillonite and water at a solid-liquid ratio of 2:100, wherein the unit of the solid-liquid ratio is g / mL, to obtain a montmorillonite suspension; mixing the montmorillonite suspension at a volume ratio of 10:25 with the aluminum pillaring solution obtained in step (1) by dropping the aluminum pillaring solution into the montmorillonite suspension; stirring at 70° C. for 2.5 h; standing and heating at 70° C. for 9 h; and centrifuging, washing, drying, grinding and sieving in sequence to obtain aluminum pillared montmorillonite.
[0114] Example 6
[0115] This embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery. The liquid-to-solid ratio of the electrolyte solution to the aluminum-pillared montmorillonite is 3:3, and the unit of the solid-to-liquid ratio is g / g. The rest is the same as that of Embodiment 1.
[0116] Example 7
[0117] This embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery. The solid-liquid ratio of the electrolyte solution to the aluminum-pillared montmorillonite is 12:3, and the unit of the solid-liquid ratio is g / g. The rest is the same as that of Embodiment 1.
[0118] Example 8
[0119] This embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, which is the same as that of Embodiment 1 except that the concentration of zinc sulfate is 0.5 mol / L.
[0120] Example 9
[0121] This embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, which is the same as that of Embodiment 1 except that the concentration of zinc sulfate is 5 mol / L.
[0122] Example 10
[0123] This embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, which is the same as that of Embodiment 1 except that the concentration of manganese sulfate is 0.05 mol / L.
[0124] Embodiment 11
[0125] This embodiment provides a quasi-solid electrolyte for an aqueous zinc ion battery, which is the same as that of Embodiment 1 except that the concentration of manganese sulfate is 0.5 mol / L.
[0126] Comparative Example 1
[0127] This comparative example provides a quasi-solid electrolyte for an aqueous zinc ion battery, wherein the quasi-solid electrolyte for an aqueous zinc ion battery comprises zinc sulfate, manganese sulfate and montmorillonite.
[0128] The preparation method of the aqueous zinc ion battery quasi-solid electrolyte comprises:
[0129] An electrolyte solution and montmorillonite having a solid-liquid ratio of 8:3 are mixed by stirring for 30 minutes and ultrasonically for 40 minutes at 20°C, wherein the unit of the solid-liquid ratio is g / g, and the electrolyte solution includes zinc sulfate having a concentration of 2.5 mol / L and manganese sulfate having a concentration of 0.2 mol / L; and the mixture is allowed to stand at 15°C for 10 hours to obtain a quasi-solid electrolyte for an aqueous zinc ion battery.
[0130] Comparative Example 2
[0131] This comparative example provides a quasi-solid electrolyte for an aqueous zinc ion battery, which is the same as Example 1 except that the electrolyte solution does not include manganese sulfate, that is, the quasi-solid electrolyte for the aqueous zinc ion battery does not include manganese sulfate.
[0132] The small-angle X-ray diffraction patterns obtained by X-ray diffraction of the aluminum-pillared montmorillonite in Examples 1 to 5 and the montmorillonite in Comparative Example 1 are as follows: Figure 1 As shown, the small-angle characteristic diffraction peak positions (2θ) and interlayer spacing of aluminum-pillared montmorillonite and montmorillonite are calculated by X-ray diffraction test results as shown in Table 1;
[0133] The specific surface areas of the aluminum-pillared montmorillonite in Examples 1 to 5 and the montmorillonite in Comparative Example 1 are shown in Table 1.
[0134] The X-ray diffraction patterns obtained by X-ray diffraction of montmorillonite, aluminum-pillared montmorillonite and aqueous zinc ion battery quasi-solid electrolyte in Example 1 are compared with the standard diffraction cards of ZnSO4 and montmorillonite (NaMgAlSiO2(OH)H2O). Figure 2 As shown;
[0135] The quasi-solid electrolyte of the aqueous zinc ion battery prepared in Example 1 was subjected to transmission test, and the TEM image obtained was as follows: Figure 3 As shown;
[0136] The quasi-solid electrolyte of the aqueous zinc ion battery in Examples 1 to 11 and Comparative Examples 1 and 2 was respectively applied to the surface of the manganese oxide electrode and the zinc electrode with a scraper to obtain a positive electrode and a negative electrode. A glass fiber membrane was used as a separator. The positive electrode, the negative electrode and the separator were assembled to obtain an aqueous zinc ion button battery. The discharge specific capacity and capacity retention rate of the aqueous zinc ion button battery after cycling were tested. The test method was:
[0137] The aqueous zinc ion button cell was subjected to a long cycle test at a current density of 0.5 A / g, and the number of cycles was 300. The results of the first coulombic efficiency, the discharge specific capacity after 300 cycles, and the capacity retention rate are shown in Table 2.
[0138] The long cycle test results of the aqueous zinc ion button cell assembled with the aqueous zinc ion battery quasi-solid electrolyte prepared in Example 1 at a current density of 0.5 A / g are as follows Figure 4 shown.
[0139] Table 1
[0140] 2e(°) Interlayer spacing (nm) <![CDATA[Specific surface area (m 2 / g)]]> Example 1 4.65 1.90 120 Example 2 4.95 1.79 72 Example 3 4.84 1.83 99 Example 4 4.70 1.88 115 Example 5 4.68 1.89 110 Comparative Example 1 5.88 1.50 36
[0141] Table 2
[0142] <![CDATA[Discharge specific capacity ( mAh / g)]]> First coulombic efficiency (%) Capacity retention rate (%) Example 1 270 96.3 98.8 Example 2 256 95.5 96.5 Example 3 258 94.8 95.6 Example 4 262 95.7 96.4 Example 5 255 94.9 95.2 Example 6 235 92.6 90.6 Example 7 224 92.3 85.2 Example 8 158 93.5 92.1 Example 9 165 90.3 84.6 Example 10 243 94.6 87.6 Embodiment 11 221 89.6 84.1 Comparative Example 1 215 88.5 85.6 Comparative Example 2 204 84.3 75.3
[0143] From Table 1 and Figures 1 to 3 We can get:
[0144] (1) It can be seen from Table 1 that, compared with montmorillonite, the small-angle characteristic diffraction peak position of the aluminum-pillared montmorillonite obtained in Examples 1 to 5 shifts to the left, and 2θ decreases; compared with montmorillonite, the interlayer spacing of the aluminum-pillared montmorillonite in Examples 1 to 5 is effectively increased, but the phase structure does not change.
[0145] (2) It can be seen from Table 1 that after montmorillonite is modified with hydroxyaluminum ions as a pillaring agent, the specific surface area of aluminum-pillared montmorillonite is greatly improved; the modification of hydroxyaluminum ions expands the specific surface area of montmorillonite, increases the contact area between the electrolyte and montmorillonite, and shortens the ion transmission path.
[0146] (2) From Figure 2 It can be seen that the diffraction peaks of the standard diffraction cards of montmorillonite and ZnSO4 exist in both the aluminum-pillared montmorillonite and the aqueous zinc ion battery quasi-solid electrolyte in Example 1, indicating that the hydroxyaluminum ions as the pillaring agent and Zn 2+ The introduction of will not change the crystal structure of montmorillonite.
[0147] (4) From Figure 3 It can be seen that the quasi-solid electrolyte for aqueous zinc ion batteries prepared in Example 1 can still maintain the layered structure of montmorillonite and is an ideal quasi-solid electrolyte material for aqueous zinc ion batteries.
[0148] From Table 2 and Figure 4 We can get:
[0149] (1) The aluminum-pillared montmorillonite obtained in Examples 1 to 5 is inserted into the SiO4-AlO6-SiO4 interlayer of the montmorillonite with a hydrated aluminum ion (hydroxyaluminum ion) having a larger ionic radius as a pillaring agent, which significantly widens the interlayer spacing and ensures that the Zn in the quasi-solid electrolyte of the aqueous zinc ion battery 2+The invention provides a fast and stable transmission and structural stability after deep cycling; the widening of the interlayer spacing correspondingly brings about an expansion of the specific surface area, provides more active sites, and shortens the transmission path of zinc ions; the aqueous zinc ion battery assembled with the quasi-solid electrolyte of the aqueous zinc ion battery of the present invention has excellent discharge specific capacity, coulomb efficiency and capacity retention rate.
[0150] (2) By comparing Example 1 with Examples 6 and 7, it can be seen that the solid-liquid ratio of the electrolyte solution to the aluminum-pillared montmorillonite of the present invention affects the discharge specific capacity, coulombic efficiency and capacity retention rate of the aqueous zinc ion button battery; when the solid-liquid ratio of the electrolyte solution to the aluminum-pillared montmorillonite is low, the discharge specific capacity, coulombic efficiency and capacity retention rate will decrease. This is because the content of the aluminum-pillared montmorillonite is too little and the ionic conductivity is too low, resulting in a decrease in the discharge specific capacity; the quasi-solid electrolyte has an insufficient gel degree, resulting in a quasi-solid electrolyte. The electrolyte does not provide enough protection for the positive and negative electrodes, which leads to the growth of dendrites and the dissolution of the positive electrode material, resulting in low coulombic efficiency and reduced capacity retention rate; when the solid-liquid ratio of the electrolyte solution to the aluminum-pillared montmorillonite is too high, the discharge specific capacity, coulombic efficiency and capacity retention rate will decrease. This is because the content of aluminum-pillared montmorillonite is too high, which leads to an increase in interface resistance and a decrease in ionic conductivity; the content of liquid electrolyte decreases, and the concentration of free zinc ions decreases, resulting in a decrease in specific capacity, coulombic efficiency and capacity retention rate.
[0151] (3) By comparing Example 1 with Examples 8 and 9, it can be seen that the concentration of zinc salt in the electrolyte solution of the present invention affects the discharge specific capacity, coulomb efficiency and capacity retention rate of the aqueous zinc ion button battery; when the concentration of zinc salt is low, the discharge specific capacity, coulomb efficiency and capacity retention rate will decrease. This is because the ionic conductivity of zinc ions decreases, the number of zinc ions is too small, and more zinc ions cannot be provided to enter manganese oxide; when the concentration of zinc salt is high, the discharge specific capacity, coulomb efficiency and capacity retention rate will decrease. This is because the concentration of zinc salt solution increases, the viscosity increases, and the ionic conductivity of zinc ions decreases; too many zinc ions will block the tunnel structure of manganese oxide, which is not conducive to charging and discharging.
[0152] (4) By comparing Example 1 with Examples 10 and 11, it can be seen that the concentration of manganese salt in the electrolyte solution of the present invention will affect the discharge specific capacity, coulomb efficiency and capacity retention rate of the aqueous zinc ion button battery; when the concentration of manganese salt is low, the discharge specific capacity will decrease, the coulomb efficiency will decrease and the capacity retention rate will decrease. This is because the dissolution inhibition ability of manganese sulfate on the positive electrode manganese oxide is weakened, resulting in more manganese ions being dissolved, resulting in a corresponding decrease in discharge specific capacity and a decrease in capacity retention rate; when the concentration of manganese salt is high, the discharge specific capacity will decrease, the coulomb efficiency will decrease and the capacity retention rate will decrease. This is because the concentration of manganese sulfate is too high, which will lead to an excessively high concentration of the overall solution, resulting in salting out, and zinc sulfate and manganese sulfate will precipitate and cover the surface of the positive and negative electrodes, resulting in an increase in interface resistance, and also an increase in cost.
[0153] (5) By comparing Example 1 with Comparative Example 1, it can be seen that the aluminum-pillared montmorillonite prepared by inserting the hydrated aluminum ions (hydroxyaluminum ions) described in the present invention as pillaring agents into montmorillonite has a greater improvement in the performance of the quasi-solid electrolyte of aqueous zinc ion batteries.
[0154] (6) By comparing Example 1 with Comparative Example 2, it can be seen that the addition of the manganese salt described in the present invention affects the discharge specific capacity, coulomb efficiency and capacity retention rate of the aqueous zinc ion button battery; the role of the manganese salt described in the present invention is to inhibit the dissolution of the positive electrode manganese dioxide.
[0155] In summary, the aluminum-pillared montmorillonite of the present invention uses hydrated aluminum ions (hydroxyaluminum ions) with larger ionic radius as pillaring agents to insert into the SiO4-AlO6-SiO4 interlayer of the montmorillonite, which significantly widens the interlayer spacing and ensures that Zn in the quasi-solid electrolyte of the aqueous zinc ion battery 2+ The fast and stable transmission and structural stability after deep cycling; the widening of the interlayer spacing correspondingly brings about the expansion of the specific surface area, provides more active sites, and shortens the transmission path of zinc ions; the aqueous zinc ion battery assembled with the quasi-solid electrolyte of the aqueous zinc ion battery of the present invention has excellent reversible capacity and cycle stability;
[0156] The invention adopts aluminum chloride solution, sodium hydroxide solution and montmorillonite as main raw materials to prepare aluminum pillared montmorillonite, and then mixes with electrolyte solution to prepare quasi-solid electrolyte for aqueous zinc ion battery; the raw materials used in the preparation method are widely available and inexpensive; the preparation method of the quasi-solid electrolyte for aqueous zinc ion battery of the invention has simple process, low experimental condition requirements, low production cost and meets the requirements of industrialization;
[0157] The present invention obtains a positive electrode and a negative electrode with a protective layer by coating a quasi-solid electrolyte of an aqueous zinc ion battery on the surface of a manganese oxide electrode and a zinc electrode, thereby preventing the acidic aqueous electrolyte from directly contacting the manganese oxide electrode and the zinc electrode, thereby inhibiting the dissolution of the manganese oxide electrode, the corrosion of the zinc electrode and the side reaction of forming a passivation layer, avoiding the problems of rapid capacity decay and internal short circuit failure of the aqueous zinc ion battery, and effectively improving the safety performance of the aqueous zinc ion battery.
[0158] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A quasi-solid electrolyte for an aqueous zinc ion battery, characterized in that: The quasi-solid electrolyte of the aqueous zinc ion battery comprises zinc salt, manganese salt and aluminum pillared montmorillonite; The preparation method of the aluminum pillared montmorillonite comprises the following steps: (1) mixing an aluminum chloride solution and a sodium hydroxide solution, and allowing the mixture to stand to obtain an aluminum pillaring solution; (2) mixing montmorillonite with water to obtain a montmorillonite suspension; then mixing the montmorillonite suspension with the aluminum pillared solution obtained in step (1), allowing the mixture to stand to obtain the aluminum pillared montmorillonite.
2. The quasi-solid electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that: The mixing in step (1) includes a first mixing and a second mixing performed sequentially; The first mixing temperature is 10 to 30° C. and the time is 1 to 10 minutes; The temperature of the second mixing is 40-80° C., and the time is 1-4 hours.
3. The quasi-solid electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that: The volume ratio of the aluminum chloride solution to the sodium hydroxide solution in step (1) is 1:(1-1.4); The concentration of the aluminum chloride solution in step (1) is 10-15 g / L; The concentration of the sodium hydroxide solution in step (1) is 6-10 g / L.
4. The preparation method according to claim 1, characterized in that: The solid-to-liquid ratio of the montmorillonite to water in step (2) is (1-5):100, and the unit of the solid-to-liquid ratio is g / mL; The volume ratio of the montmorillonite suspension to the aluminum pillar solution is 10:(5.5-42).
5. The preparation method according to claim 1, characterized in that: The mixing temperature in step (2) is 40 to 80° C. and the mixing time is 1 to 4 hours; The standing temperature in step (2) is 40 to 80° C. and the standing time is 6 to 18 hours.
6. A method for preparing a quasi-solid electrolyte for an aqueous zinc ion battery as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises: The electrolyte solution and the aluminum pillared montmorillonite are mixed and allowed to stand to obtain a quasi-solid electrolyte for an aqueous zinc ion battery; The electrolyte solution includes zinc salt and manganese salt.
7. The preparation method according to claim 6, characterized in that: The mixing temperature is 10-30°C and the mixing time is 40-80min; The standing temperature is 10-30° C. and the standing time is 8-12 hours.
8. The preparation method according to claim 6, characterized in that: The liquid-to-solid ratio of the electrolyte solution to the aluminum-pillared montmorillonite is (5-10):3, and the unit of the liquid-to-solid ratio is g / g; The concentration of zinc salt in the electrolyte solution is 1 to 3 mol / L; The concentration of the manganese salt in the electrolyte solution is 0.1-0.3 mol / L.
9. An application of the quasi-solid electrolyte for aqueous zinc ion batteries as claimed in any one of claims 1 to 5, characterized in that: The application includes: coating a quasi-solid electrolyte of an aqueous zinc ion battery on the surface of a first electrode and a second electrode respectively to obtain a positive electrode and a negative electrode; and assembling the positive electrode, the negative electrode and a diaphragm to obtain an aqueous zinc ion battery.
Citation Information
Patent Citations
Composite quasi-solid electrolyte, preparation method and total battery
CN111463481A
Composite quasi-solid-state electrolyte and preparation method thereof, and lithium battery or lithium ion battery containing composite quasi-solid-state electrolyte
CN107645013A
Lithium battery solid electrolyte based on aluminum pillared clay and preparation method thereof
CN109768321A
